Faktor-Faktor Yang Mempengaruhi Likuiditas Pada Bank Umum Syariah Di Indonesia - windari windari (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to determine the effect of NPF, CAR and ROA partially and simultaneously on the FDR of Islamic Commercial Banks in Indonesia. This type of research is a quantitative research. The data source used is secondary data taken through the website www.ojk.co.id. The form of data in this study uses time series data as many as 60 samples. technical analysis using eviews, godnes and fit, t test and F test. The results of regression measurement with the equation FDR = 18249,622 -7,498NPF -3,589CAR - 0,721ROA and R square data of 68.6 percent, while the rest is 31.4 percent is influenced by other variables not included in this model. The result of the research partially (t test) states that -titung <-table (-7,829 <-2.003) and the significance value <0.05 (0,000 <0.05) means that H1 is accepted, meaning that NPF partially and significantly affects FDR